Community livelihood assets of forest village management in Nanga Lauk Village, Kapuas Hulu District, West Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Roslinda E, Sabathino P, Pratama YA, Supriadi, Eva J. 2024. Community livelihood assets of forest village management in Nanga Lauk Village, Kapuas Hulu District, West Kalimantan, Indonesia. Biodiversitas 25: 664-672. Village forest is a community-based forest management scheme in the social forestry program. At the same time, the management of village forest is local village communities that fulfill their daily needs by utilizing existing natural resources. Nanga Lauk Village Forest Management has successfully carried out activities on the social forestry program. This study aims to explain the livelihood system of the Nanga Lauk Village community to meet the family's living needs in managing the village forest. The study was conducted using a survey method in Nanga Lauk Village, Kapuas Hulu District, West Kalimantan, Indonesia, and the community was used as informants. Data were collected through observation, in-depth interviews guided by a list of questions, documentation, and a review of supporting literature. Data analysis was carried out descriptively, qualitatively and by Pentagon asset analysis. The assets owned by the people of the Nanga Lauk Village are resources of human, natural, financial, social, and physical. Natural and physical resources are the main assets used by society to meet life's needs, followed by social, human, and financial. So, the strategy that can be implemented is a consolidation based on socio-economic status. Meanwhile, based on activities to increase income, the community can apply livelihood strategies in agricultural sectors because of abundant natural resources. Skill training is needed for the community because a low level of human assets will shape the mindset of farmers regarding their inability to do other work on the side which should be able to improve their standard of living.
Keywords: Agriculture, consolidation strategy, livelihood, sustainability, village forest